Positioning Women Entrepreneurs in Small and Medium Enterprises in Indonesia – Food & Beverage Sector - Sutrisno; Pandu Adi Cakranegara; Eka Hendrayani; Jean Richard Jokhu; Muhammad Yusuf (Enrichment : Journal of Management, 2022)
The food and beverage industry is a significant business sector in Indonesia. Indonesian women are known to dominate the SMEs in this sector. There is a major reason for the dramatic increase in female entrepreneurs in Indonesia. Unfortunately, a lack of success and sustainability factors is a current barrier for a culinary business. The goal of this research is to identify the characteristics of today's female entrepreneurs and to look into the gap between the wave of female entrepreneurs and business sustainability. Research questions help to strengthen the problem statement by determining the research objectives. Researchers pose four research questions, followed by four hypotheses. To evaluate research work, this study employs a qualitative methodology. 108 female entrepreneurs were surveyed and interviewed by the researchers. The findings of the study highlight the primary reasons, failure factors, success factors, and obstacles to running.